1982
DOI: 10.1021/i200019a010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH on the removal of pyritic sulfur from coal by oxydesulfurization

Abstract: Baker, C. G. J.; Bergougnou, M. A. Can. J . Chem. Eng. 1972, 50, 695. Kim, S. D.; Baker, C. 0. J.; Bergougnou, M. A. Can. J. Chem. Eng. 1975, 53, 134. KO&, K.; MarWka, S.; Ueyama, K.; Matsurra, A.; Yamashlta. F.; Iwamoto, S.; Kato, Y.; Inoue. H.; Shloeta. M.; Suzuki, S.: Akehata, T. J . Chem.The effect of pH on the removal of pyritic sulfur in airlwater chemical coal cleaning was investigated. The pH was varied by adding sulfuric acid or sodium carbonate to a coal-water slurry. The effect of nearby neutral pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…They have observed that the rate of reaction is second order in pyritic sulfur based on the continuous reaction model as reported by Slagle et al (1980). Joshi et al (1982) have studied the effect of pH on the removal of pyritic sulfur from coal by oxydesulfurization. Their observations indicate that the rate of pyrite oxidation is at a minimum at nearly neutral conditions.…”
Section: Chowdhury Andmentioning
confidence: 96%
See 1 more Smart Citation
“…They have observed that the rate of reaction is second order in pyritic sulfur based on the continuous reaction model as reported by Slagle et al (1980). Joshi et al (1982) have studied the effect of pH on the removal of pyritic sulfur from coal by oxydesulfurization. Their observations indicate that the rate of pyrite oxidation is at a minimum at nearly neutral conditions.…”
Section: Chowdhury Andmentioning
confidence: 96%
“…Under otherwise identical conditions, the rate of pyrite oxidation is reported to be greater in basic pH than in acidic pH. These enhancements in the rate of pyrite oxidation have been explained on the basis of electrochemical reactions [Joshi et al (1982)]. Joshi et al (1983) have reported the effect of particle size in the air/water chemical coal cleaning.…”
Section: Chowdhury Andmentioning
confidence: 99%